Environmental characterization of the landscape of the municipality of Itirapina/SP - Santos, Bruna Felix dos; Trevisan, Diego Peruchi; Moschini, Luiz Eduardo (Revista Hipótese, 2018)
In recent years, the concern for the preservation of natural resources, soil and water has increased significantly. The present study had as objective to carry out the environmental characterization of the landscape in Itirapina-SP. The information of hydrography, hypsometry, slope, geology, pedology, road mesh and use and land cover were elaborated. The presence of rural characteristics was observed, having its economic sector based mainly on the cultivation of sugarcane.
Keywords: Anthropogenic Actions; Preservation of natural resources; Environmental characterization of the landscape